Behind China's "great Cultural Revolution" - Shu-tse, Peng; Frank, Pierre; Hansen, Joseph; Novack, George (New York: Merit Publishers, 1967)
"By Peng Shu-tse, Pierre Frank, Joseph Hansen, George Novack Bibliotheek François Vercammen"